Model Management Conflict of Minning Through Social Capital Approach - Sulsalman Moita (International Journal of Integrative Sciences, 2024)
This study aims to understand and identify the dynamics and forms of mining conflicts, and to formulate and produce models of mining conflict resolution through an approach of social capital in the region Bombana gold mine. The results showed that the dynamics and other forms of conflict. The research was conducted in Bombana Southeast Sulawesi Province using qualitative methods. Data collection techniques are in-depth interviews, observation, and study the document; while data analysis is qualitative analysis techniques. The results showed dynamics of mining conflicts and forms of conflict that put the three typologies of conflict horizontal, vertical conflicts and conflicts of interest. These conflicts occur simultaneously on groups that have an interest in the results of the gold mines, such as illegal, local communities, mining operators, government. Furthermore, mining of conflict settlement through the mechanism of social capital puts the power elements of social capital, such as the element of mutual trust, reciprocal relations element, the element values and social norms, and social networking elements